A new forest lizard fauna from Caribbean islands (Squamata, Diploglossidae, Celestinae) - Schools, Molly; Hedges, S. Blair (Zootaxa, 2024)
The taxonomy of Neotropical forest lizards (Diploglossidae) has been the subject of controversy because of a paucity of diagnostic characters and genetic data. Recent molecular studies have produced phylogenies that are highly supported but have few individuals represented for each species. These studies have corrected generic names and defined new genera and subfamilies in Diploglossidae. However, they have shown that multiple species are not monophyletic or have high levels of genetic divergence, indicating the need to define new species. Three subfamilies, 12 genera, and 56 species of diploglossid lizards are currently recognized; 25 of these are in the subfamily Celestinae. We conducted a systematic revision of Caribbean celestine forest lizards (from the Cayman Islands, Jamaica, and Hispaniola) using DNA sequence data from 372 individuals, supplemented by both conventional and unconventional morphological characters from 958 preserved specimens. In some cases, we obtained DNA sequence data from museum specimens, including types, nearly 200 years old. We propose and use a new species delimitation method based on time of divergence. We define 17 new species, elevate 17 subspecies, and elevate one species from synonymy, resulting in 35 newly recognized species. Additionally, we synonymize two pairs of previously recognized subspecies and one pair of species. This increases the number of celestine species from 25 to 59 and raises the total number of diploglossids to 90 species. Of those, 63 occur on Caribbean islands and all are endemic to those islands. Fourteen Caribbean celestine species (24%) are Critically Endangered, 17 species (29%) are Endangered, and 1 species (2%) is Vulnerable, resulting in a proportion of threatened species (54%) more than twice as high as the average for reptiles, based on IUCN Redlist criteria. Three of the Critically Endangered species are possibly extinct because of human activities during the last two centuries. Several of the surviving species are near extinction and in need of immediate protection. Extensive forest loss on Caribbean islands has led to the decline of Caribbean forest lizards, which rely on forests as their primary habitat. In addition to deforestation, the introduction of the Small Indian Mongoose is in part responsible for the decline of Caribbean diploglossid lizards. That invasive predator was introduced as a biological control of rats in sugar cane fields in the late 19th Century (1872–1900), immediately resulting in a mass extinction of reptiles. The ground-dwelling and diurnal habits of diploglossids have made them particularly susceptible to mongoose predation.